If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1y = 3y + -2 Reorder the terms: 8 + -1y = -2 + 3y Solving 8 + -1y = -2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 8 + -1y + -3y = -2 + 3y + -3y Combine like terms: -1y + -3y = -4y 8 + -4y = -2 + 3y + -3y Combine like terms: 3y + -3y = 0 8 + -4y = -2 + 0 8 + -4y = -2 Add '-8' to each side of the equation. 8 + -8 + -4y = -2 + -8 Combine like terms: 8 + -8 = 0 0 + -4y = -2 + -8 -4y = -2 + -8 Combine like terms: -2 + -8 = -10 -4y = -10 Divide each side by '-4'. y = 2.5 Simplifying y = 2.5
| 5n^2+40n+60= | | 8x+6=-4+3x+20 | | 5x^2-20x+10= | | n^2-8n+12= | | 200=(x+y)4 | | cos(0.5)= | | sin(1)= | | 5x-5y=200 | | x+0.05x=6720 | | cos(1)= | | 4(5x-7)-2(4x+1)=6 | | -4x^2+8x-12= | | p^2+2p-3= | | cos(0)+sin(0)= | | m^2+32=12m | | 1/3y=5x-2 | | 1=6x^2+5 | | ln(x+1)-ln(x)= | | a^2-3a-48=0 | | sin(0)+cos(1)= | | 5(z-5)+4z-3= | | 10s^2-4s=2s | | 5x^2+16x=-3 | | -3(2x-4)+8x-5= | | (20x)/(((x^2)-4)^2) | | p^2+p-3= | | 2x×6=11x-3/4 | | (3-k)x+y+2=0 | | -a^2-11a-18= | | 2lnx-3ln(1/x)=10 | | 56/g= | | 0.4(5-04n)=3.2 |